METODIST FAOLIYATI ASOSLARI - Sidiqova Yulduz Sobirovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
This article analyzes the role of the teacher in the organization of preschool education, the tasks that he must perform, as well as qualification requirements.